Erdheim–Chester disease misdiagnosed as meningioma of the pontocerebellar angle: A case report and review of literature - Ali Riza Guvercin; Beyhan Guvercin; Emel Çakır; Uğur Yazar (Indian Journal of Pathology and Microbiology)
Erdheim–Chester Disease (ECD) is a rare non-Langerhans form of systemic histiocytosis of unknown etiology with multiple organ involvement. It most commonly affects the long bones, lungs, heart, retroperitoneum, eyes, and kidneys and less commonly the brain and spinal cord. Although there are very few cases of supratentorial ECD mimicking intracranial meningioma reported in literature, to the best of our knowledge, there are no reports on ECD mimicking infratentorial pontocerebellar angle meningioma. The present study reports a case of ECD mimicking pontocerebellar angle meningioma. This study aimed to emphasize the importance of systemic evaluation using a multidisciplinary approach as well as the need for considering ECD as a differential diagnosis of xanthomatous meningioma.